Malaysian private higher education undergraduates’ digital reading habits and attitudes towards reading - Osman, Syamsul Fozy; Hashim, Che Noraini; Sheikh Ahmad, Ismail (2016)
Reading is an acknowledged avenue for the generation of interactive metacognitive skills that lead to higher order thinking skills, known to generate literary skills that develop maturity in thinking and thoughts, a tool for the enhancement of language skills and confidence as well as a catalyst that promotes values, initiative, motivation and environment that encourage self learning for improved academic performance. This study is an attempt to identify a higher education institution’s undergraduates’ digital reading habit and attitudes towards reading. It took the quantitative approach and a questionnaire was employed to collect data. The questionnaire investigates three kinds of information, the first; information on the demographics of the group, secondly, their digital reading habit that seeks to identify their internet activities, the types of digital reading content frequently read, the online news portal frequented, the news portal content favored, and the social network groups that they perceive as encouraging reading and finally the identification of their attitudes towards reading employing Smith’s (1991) Adult Survey of Reading Attitude (ASRA) . Findings indicate that the respondents’ digital reading habits are inclined towards entertainment based content and their reading attitude indicate the respondents as reluctant readers with a negative disposition on reading. The paper is concluded with some suggestions to promote the digital reading habit.